Development of assessment tool for micro and small business enterprises based on the level of awareness on business management practices among general merchandise store owners - Barcia, James Michael B.; Beltran, Kyla Nicole M.; Latoja, Jezzel G.; Mifor, John Patrick A. (b)
General merchandise stores in the Philippines are valued for their convenience, wide product range, and competitive pricing, appealing to budget-conscious shoppers. These stores provide a one-stop shopping experience, offering essentials and non-essentials (Dionola et al., 2021; Decker, 2019). In competitive urban areas like Las Pinas City, effective business management is crucial for success, as these stores play a vital role in the local economy by creating jobs and supplying essential goods. This study assessed the relationship between the level of awareness and the frequency of implementation of business management practices among general merchandise store owners, focusing mainly on budget planning, performance planning, staffing, and controlling. Researchers adapted the descriptive quantitative research design, focusing on the 22 general merchandise stores under sole proprietorship in Pulang Lipa Uno, selected through total population sampling. Data were collected using a validated 45-item self-made questionnaire. Statistical tools such as frequency and percentage, weighted mean, t-test, ANOVA, and Pearson R were used to examine and interpret the gathered data. The data collected revealed that while the chosen respondents were {93}aware{94} of business management practices, they {93}often implement{94} them, facing challenges in cost reduction and employee incentives. It was also found that there were no significant differences in awareness and implementation of practices based on profile variables. Moreover, a positive correlation was found between awareness levels and the frequency of implementation management practices. With these findings and conclusions, the researchers recommend using employee feedback forms, training on key management challenges, creating a mentorship program for less experienced owners, and organizing workshops or networking events to share best practices.
Undergraduate thesis.
Keywords: Micro and small businesses; Business management practices; Awareness; Implementation; MSEs